2012
DOI: 10.4274/tftr.83723
|View full text |Cite
|
Sign up to set email alerts
|

Ailesel Kamptodaktili ve Periferik Nöropatili Üç Kız Kardeş

... ...

Abstract: Sum maryComplex regional pain syndrome (CRPS) is a painful and disabling disorder that can affect one or more extremities. The pathophysiology of CRPS is not clear but peripheral and central sensitization resulting in neurogenic inflammation has been held responsible. A 66-year-old male patient was admitted to our outpatient clinic with complaints of swelling, pain, warmth, and restriction in movements of the left upper extremity after a snake bite. Electromyographic evaluation was compatible with toxic neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Complex regional pain syndrome incited by a snake bite is infrequent, as demonstrated by a medical literature research yielding only four reported cases worldwide. To the best of our knowledge, this is the first CRPS case reported after snakebite in the United States [5][6][7][8]. One known hypothesis suggests that snake venom can play a role in causation or exaggeration of CRPS added to the role of local inflammation, pain, and tissue damage [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex regional pain syndrome incited by a snake bite is infrequent, as demonstrated by a medical literature research yielding only four reported cases worldwide. To the best of our knowledge, this is the first CRPS case reported after snakebite in the United States [5][6][7][8]. One known hypothesis suggests that snake venom can play a role in causation or exaggeration of CRPS added to the role of local inflammation, pain, and tissue damage [5].…”
Section: Discussionmentioning
confidence: 99%
“…Complex regional pain syndrome was first described in 1994, and it is hypothesized that phospholipase A2, metalloproteinase, inflammatory substances such as interleukins and tumor necrosis factors, along with toxicities from snake venom are implicated in local tissue effects and may play a role in the development of CRPS [4][5]. Increased sensitivity to catecholamines due to sympathetic denervation and upregulation of peripheral receptors have also been proposed as pathogenic mechanisms [6]. The estimated incidence of CRPS is 5.5-26.2 cases per 100,000 people per year, but the occurrence of CRPS after a snake bite is very rare with only four cases reported worldwide and none reported in the United States to our knowledge [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, four cases have been reported to date. [6][7][8][9] The present report is the first in the United States, though the rarity seems more apparent than real considering that some snakebite victims continue to complain of pain accompanied by vasomotor symptoms years after envenomation.…”
Section: Introductionmentioning
confidence: 88%